Acute inhibition of TAK1 protects against neuronal death in cerebral ischemia - Neubert, M.; Ridder, D. A.; Bargiotas, Panagiotis; Akira, S.; Schwaninger, Markus (Cell death and differentiation, 2011)
Neuronal apoptosis contributes to ischemic brain damage and neurodegenerative disorders. Key regulators of neuronal apoptosis are the transcription factor NF-κB and the MAP kinases p38/MAPK and JNK, which share a common upstream activator, the mitogen-activated protein kinase kinase kinase (MAP3K) TGFβ-activated kinase 1 (TAK1). Here we investigate the function of TAK1 in ischemia-induced neuronal apoptosis. In primary cortical neurons, TAK1 was activated by oxygen glucose deprivation (OGD), an in vitro model of cerebral ischemia. We found that short-term inhibition of TAK1 protected against OGD in vitro and reduced the infarct volume after middle cerebral artery occlusion in vivo. Prolonged inhibition or deletion of the TAK1 gene in neurons was, however, not protective. Short-term, but not prolonged inhibition of TAK1 interfered with the activation of p38/MAPK and JNK by OGD, the induction of the pro-oxidative genes Cox-2, Nox-2, and p40phox, and the formation of superoxide. We found that prolonged TAK1 inhibition upregulated another MAP3K, apoptosis signal-regulating kinase-1, which is able to compensate for TAK1 inhibition. Our study demonstrates that TAK1 is a central target for short-term inhibition of key signaling pathways and neuroprotection in cerebral ischemia.